A Multi-Zone HVAC System for a Typical Building for MATLAB/SIMULINK Platform - Ahmad Parvaresh; Seyed Mohammad Ali Mohammadi (Institute of Advanced Engineering and Science, 2013)
Matlab/Simulink is known in a large number of fields as a powerful and modern simulation tool. In the field of building and HVAC simulation its use is also increasing. However, it is still believed to be a tool for small applications due to its graphical structure and not to fit well for the simulation of multi-zone buildings. This paper presents the development of a new multi-zone building model for Matlab/Simulink platform.